Measurement of Harm Outcomes in Older Adults after Hospital Discharge: Reliability and Validity - Alison Douglas; Lori Letts; Kevin Eva; Julie Richardson (Journal of Aging Research)
Objectives. Defining and validating a measure of safety contributes to further validation of clinical measures. The objective was to define and examine the psychometric properties of the outcome “incidents of harm.” Methods. The Incident of Harm Caregiver Questionnaire was administered to caregivers of older adults discharged from hospital by telephone. Caregivers completed daily logs for one month and medical charts were examined. Results. Test-retest reliability (n=38) was high for the occurrence of an incident of harm (yes/no; kappa = 1.0) and the type of incident (agreement = 100%). Validation against daily logs found no disagreement regarding occurrence or types of incidents. Validation with medical charts found no disagreement regarding incident occurrence and disagreement in half regarding incident type. Discussion. The data support the Incident of Harm Caregiver Questionnaire as a reliable and valid estimation of incidents for this sample and are important to researchers as a method to measure safety when validating clinical measures.